Un panno medievale dell'azienda pratese di Francesco Datini Studio e ricostruzione sperimentale - Degl'Innocenti, Daniela; Nigro, Giampiero (Biblioteca di storia, 2021)
The volume concludes a multi-year study conceived and carried out by the Museo del Tessuto of Prato, which involved public bodies and cultural institutions in the city motivated by the desire to see one of the identifying products of the Prato textile district returned to contemporary life: its cloth. The idea to experimentally reconstruct the cloth arose from the study of some documents of the Datini Fund, a unique archival complex in the world for historical and economic studies on the Middle Ages. The collective and interdisciplinary project is documented in a volume created in collaboration with the International Institute of Economic History "F. Datini". The historical contributions on the manufacturing and commercial management of the Datini cloth are followed by a second part that documents the study and experimentation phases of its reconstruction.